Acut toxicity of cupper sulphate (CuSO4• 5 H2O) on medical leech Hirudo medicinalis L. 1758 - Saglam, Naim; Sahin, Aysegul (Ege Univ, Fac Fisheries, 2006)
In this study acut toxicity effect of cupper sulphate on medical leech Hirudo medicinalis was investigated. For this purpose, 0,025 ppm, 0,05 ppm, 0,1 ppm concentrations of cupper sulphate for were applied to leeches as bath for 96 h. 96 h - LD50 value was observed as 0.0044 ppm. In addition, severe mucous and hemoragie were observed in leeches. Death periods of leeches were also observed for each dosages.
Keywords: Leech; Hirudo medicinalis; Cupper sulphate; Acut Toxicity; Lethal concentrations; lethal times